Facile preparation of new polystyrene leucomalachite green thick films and study of their radiochromic behavior for low doses of gamma radiation - Bera, Anuradha; Malav, Shatrughan; Tiwari, Bajrang Lal; Vaijapurkar, Shyam Govind (International Journal of Advanced Chemistry, 2017)
Colourless polystyrene-leucomalachite green (PS-LMG) thick films containing a suitable chloroalkane were prepared by a fast and facile casting method, and were investigated for their radio chromic response behavior under the influence of 1.25 MeV Î³-radiation. Their gamma response was studied in the 0.05 kGy to 10 kGy range to evaluate their suitability for potential use as the dosimeter in the radiation processing industries. The films were found to undergo a visibly distinct green coloration in the studied range, with the colour intensity increasing with an increase in the total dose. The radiochromic response of these films when investigated as a function of film thickness showed that the colour development as well as the linearity of the response was markedly affected by the thickness of the films. The effect of dye loading and the chloroalkane concentration on the radiochromic response of these films were also investigated. Depending upon the film thickness and reactant concentrations, the films were found to be capable of visually detecting gamma radiation doses as low as few tens of grays.